"What's next? Calling beer-drinking a sport?!": virtual resistance to considering eSport as sport. Issue 1 (23rd September 2020) - Tjønndal, Anne
Abstract : Purpose: The purpose of this paper is to study virtual resistance towards the introduction of Norway's first professional eSport league in the category of sport video games (SVGs), Eserien – the professional FIFA league and its inclusion in the Norwegian Football Federation. Design/methodology/approach: A qualitative content analysis of texts published from the first season of Eserien was launched (December 2018) and during the first season of Eserien (April 2019 to December 2019) in Norwegian online spaces. Based on this approach, a total of 23 texts were subjected to a qualitative content analysis. The theoretical framework for the analysis of the material is Guttmann's (1978/2004) characteristics of modern sport and processes of sportification, as well as conceptualizations of the sport-health ideology in national and international sport policies today. Findings: The arguments made against the inclusion of the professional FIFA league Eserien as part of the Norwegian Football Federation revolves around three main themes: (1) eSport as something unhealthy and inactive, (2) issues of cheating and match fixing in professional eSports and (3) threats professionalized eSport poses for traditional football clubs and players in terms of securing sponsorship and gaining media attention. Research limitations/implications: A limitation is the small sample size consisting of data from the first season of the first professional FIFA league organized by a Norwegian governing sport body. More research is needed to support the results found here, and readers should be careful to transfer the findings from this study to other sporting contexts. Originality/value: This study is an empirical exploration of resistance towards eSport expressed by traditional sport fans. These insights expand on existing sport management research on spectators, commercialization and professionalization of eSport.